Mechanistic insights on 1-butene polymerization catalyzed by homogeneous single-site catalysts: a DFT computational study - D’Anania, Olga; De Rosa, Claudio; Talarico, Giovanni (Frontiers in Chemistry, 2024)
Isotactic poly(1-butene) (iPB) is an interesting semi-crystalline thermoplastic material characterized by notable physical and mechanical attributes encompassing superior creep and stress resistance, elevated toughness, stiffness, and thermal endurance. These distinctive features position iPB as a viable candidate for specific applications; however, its widespread utilization is hindered by certain inherent limitations. Indeed, iPB manifests an intricate polymorphic behavior, and the gradual and spontaneous transition of the kinetically favored form II to the thermodynamically favored form I during aging introduces alterations to the material's properties. Despite its potential, the attainment of iPB with an exceedingly high molecular mass remains elusive, particularly when employing homogeneous catalysts renowned for their efficacy in propene polymerization. In this study we analyze the mechanistic aspects governing 1-butene polymerization by using DFT calculations modelling the regioselectivity of 1-butene insertions and the termination reactions occurring after primary (1,2) and secondary (2,1) insertions. Finally, the isomerization pathways leading to the formation of 4,1 units in iPB samples synthesized by homogenous catalysts is also discussed. All these aspects, furnish a mechanistic picture of the main drawbacks of an “old” but still interesting material.